Reduced loss of NH3 by coating urea with biodegradable polymers, palm stearin and selected micronutrients - Junejo, Nasima; Yusop, Mohd Khanif; Musa, Mohamed Hanafi; Dharejo, Khalil Ahmed; Wan Yunus, Wan Md. Zin (Academic Journals, 2011)
In agricultural lands, the loss of NH3 from surface-applied urea and micronutrient deficiencies are the two most common problems, which can be solved by using coated urea with micronutrients and biodegradable natural materials. These coatings can improve the nutrient status in the soil and simultaneously reduce nitrogen loss from urea. To control ammonia loss and urea’s hydrolysis process, two laboratory studies were conducted to compare the effects of using coated urea with that of using only urea. Both studies consisted of consecutive incubation experiments that were conducted on the same Typic Paleudult soil (Serdang Series). Eight treatments (labeled as Urea, UPS1, UPS2, UPS3, UAG1%, UAG2%, UG1% and UG2%) in study 1 and six treatments (labeled U, UPSCu, UAGCu, UGCu, UCu, and UCuZn) in study 2 were prepared and used to determine the effects of various concentrations of natural materials and the inhibitory effects of micronutrients on both ammonia loss and the hydrolysis process. The NH3 loss was measured by forced draft techniques; the soil’s exchangeable ammonium, available nitrate and urea-N were determined by using standard procedures. The outcomes of the study did not show any significant difference among various concentrations of natural material. Coated urea treatments significantly reduced ammonia loss by 30 to 40% in study 1 and by 40 to 67% in study 2 in comparison to urea alone. The same observation was made with respect to urea hydrolysis. All of the coated urea treatments significantly slowed down the hydrolysis process in comparison to urea. The outcomes of the study may improve urea fertilizer by reducing the loss of NH3 volatilization.